Characterization of the E-cadherin/catenin complex in colorectal carcinoma cell lines. - El-Bahrawy, M; Poulsom, R; Rowan, A; Tomlinson, I; Alison, MR; Poulsom, SR; Tomlinson, I (2004)
The E-cadherin/catenin complex is a prime mediator of cell-cell adhesion. APC mutations can result in loss of beta-catenin downregulation and an accumulation of beta-catenin in the cell. Beta-CATENIN mutations can have a similar effect. The aim of this study was to investigate the effect of beta-CATENIN and APC mutations on the expression and assembly of the E-cadherin/catenin complex. Five colorectal carcinoma cell lines with different APC and beta-CATENIN gene status were selected and mutations were confirmed. The expression of members of the E-cadherin/catenin complex was studied by immunohistochemistry and Western blotting. Complex assembly was investigated by immunoprecipitation. It is shown that E-cadherin and catenins are expressed in colorectal carcinoma cell lines with the predominant complex assembly being E-cadherin/beta-catenin/alpha-catenin. The subcellular distribution of the proteins is influenced by cell-cell contact, resulting in membranous localization. The expression and assembly of the E-cadherin/catenin complex does not appear to be affected by the presence of APC and or beta-CATENIN mutations.